2018
DOI: 10.1049/iet-nbt.2017.0302
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐induced heating for in situ DNA replication and detection in microchannels

Abstract: This study proposes a method for in situ local deoxyribonucleic acid (DNA) replication and detection in a long DNA strand through laser-induced heating and strong avidin-biotin binding. To achieve the target DNA replication, dielectrophoresis was generated to stretch and immobilise DNA strands on both ends of the electrode. Subsequently, local DNA sequences were replicated using thermal cycles generated by laser-induced heating. Replicated double-stranded DNA products were captured in situ on a solid surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The duplicated local DNA sequence could be recognized after six laser-induced heat cycles. The proposed method should make biosample gene sequence analysis more efficient (Hung & Chen, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The duplicated local DNA sequence could be recognized after six laser-induced heat cycles. The proposed method should make biosample gene sequence analysis more efficient (Hung & Chen, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Min-Sheng Hung and Ying-Ting Shih Department of Biomechatronic Engineering, National Chiayi University, Chiayi, Chiayi, Taiwan (Republic of China) DNA encodes the genetic information of all the inheritable characteristics of an organic structure. In a previous study, we proposed and demonstrated a microfluidic platform integrated with laser-induced heating for real-time replication and detection of lDNA [1,2]. Avidin-biotin binding was utilized to immobilize one end of the replicated products to the microchannels for the target sequences detection following replication.…”
Section: Dna Replication Of Single Cell Using Laser Heating In Varied Osmotic Solutionsmentioning
confidence: 99%
“…One fluorescent labelling technique that can be applied is the use of quantum dots (QDs), which have narrow emission spectra and stable fluorescent luminance. Additionally, detecting QD fluorescent luminance with a fluorescence microscope is simple and highly sensitive [5,6]. To detect plant virus, we used magnetic beads to be evenly mixed and virus gene sequences captured in the microchannels.…”
mentioning
confidence: 99%